-0.8x+0.3x-6=-7

Simple and best practice solution for -0.8x+0.3x-6=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.8x+0.3x-6=-7 equation:


Simplifying
-0.8x + 0.3x + -6 = -7

Reorder the terms:
-6 + -0.8x + 0.3x = -7

Combine like terms: -0.8x + 0.3x = -0.5x
-6 + -0.5x = -7

Solving
-6 + -0.5x = -7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -0.5x = -7 + 6

Combine like terms: -6 + 6 = 0
0 + -0.5x = -7 + 6
-0.5x = -7 + 6

Combine like terms: -7 + 6 = -1
-0.5x = -1

Divide each side by '-0.5'.
x = 2

Simplifying
x = 2

See similar equations:

| -8.9+5x-6.3+3x-2.5=5.6+9x+1.2 | | (x+6)/4-(x)/2=-x | | 3x-52=26 | | 4[2x+5]-8=36 | | 2n-15=19 | | 7w/4+3=9w/10+6 | | -x+3=16 | | 3a+2=5a-3 | | 10n-5=65 | | -5/7*7/5=-1 | | 5k^4/36k^4 | | 5x=6x+2 | | 10-5=65 | | 50/35 | | 2x^3-5x^2-x+3=0 | | 3a-5=6a+7 | | u^2/-3w^4 | | x+3y=-14 | | 2x^4+(2+2b)x^3+(-10+2b)x^2+(2-12b)x-12=0 | | 40.77=y/5+2.4y+7/10 | | 4.9k=19.11 | | 4[9+3t]-12=-6 | | -7(m+1)-m-10=-8(m+3)+7 | | 11x+14y=13 | | 2x+4=4x+3 | | -8-2(a+1)=9+a | | 0.2x-4=12 | | 16+p=4 | | N/5=4.6 | | 1/5(2x-6)=7 | | N/15=6 | | 5[2x-3]+8=9 |

Equations solver categories